Trident K9 warriors : my tales from the training ground to the battlefield with elite Navy SEAL canines - Ritland, Mike (St. Martin's Press, 2013)
Ritland started his own company training and supplying dogs for the SEAL teams, U.S. Government, and Department of Defense. In "Trident K9 Warriors" he gives readers an inside look at these elite canines--who they are, how they are trained, and the extreme missions they undertake saving countless lives, asking for little in the way of reward.